GLOBALIZING RURAL MARKETS: EVIDENCE FROM HANDMADE TRADITIONAL PRODUCT MARKETS - Vanaja Menon Vadakepat and Faisal Al Khateeb (GLOBAL JOURNAL OF BUSINESS RESEARCH, 2012)
Learning market realities improves businesses. Kerala, India, traditional cottage units producing indigenous handmade goods are not an exception. Changes because of globalization have intensified competition to imported non-natural factory products into Kerala markets. Traditional industries, ignorant of these penetrations, struggle hard to challenge their urban competitors. Response delays may push these units out, replacing them with imported products. This study carries a market threat analysis to appraise current market realities for traditional products of Kerala. The first part of the study involves a competitor analysis with a survey focusing on 200 artisans selected from three districts. We focus on five market key causes. The primary survey focused on a sample of 200 artisans randomly selected from voluntary traditional craft units of three districts. Competitive profiles developed in this paper assessed the market realities and global challenges for handmade products. The second part of the analysis, studies the types of threat that could wreak havoc the future of handmade traditional products.